Photoswitching the Efficacy of a Small‐Molecule Ligand for a Peptidergic GPCR: from Antagonism to Agonism. (6th August 2018) - Gómez‐Santacana, Xavier; de Munnik, Sabrina M.; Vijayachandran, Prashanna; Da Costa Pereira, Daniel; Bebelman, Jan Paul M.; de Esch, Iwan J. P.; Vischer, Henry F.; Wijtmans, Maikel; Leurs, Rob
Abstract: For optical control of GPCR function, we set out to develop small‐molecule ligands with photoswitchable efficacy in which both configurations bind the target protein but exert distinct pharmacological effects, that is, stimulate or antagonize GPCR activation. Our design was based on a previously identified efficacy hotspot for the peptidergic chemokine receptor CXCR3 and resulted in the synthesis and characterization of five new azobenzene‐containing CXCR3 ligands. G protein activation assays and real‐time electrophysiology experiments demonstrated photoswitching from antagonism to partial agonism and even to full agonism (compound VUF16216). SAR evaluation suggests that the size and electron‐donating properties of the substituents on the inner aromatic ring are important for the efficacy photoswitching. These compounds are the first GPCR azo ligands with a nearly full efficacy photoswitch and may become valuable pharmacological tools for the optical control of peptidergic GPCR signaling.